Diagnostic Performance of 18F-FDG PET(CT) in Bone-Bone Marrow Involvement in Pediatric Neuroblastoma: A Systemic Review and Meta-Analysis. (16th June 2021) - Sun, Lixin; Zhang, Bingye; Peng, Ruchen
Abstract : Objective . We sought to perform a systemic review and meta-analysis of the diagnostic performance of 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (computed tomography) (PET(CT)) in detection of bone and/or bone marrow involvement (BMI) in pediatric neuroblastoma (NB). Materials and Methods . We searched electronic databases Pubmed and Embase to retrieve relevant references. We calculated pooled sensitivity, specificity, positive and negative likelihood ratios (LR+ and LR−), diagnostic odds ratio (DOR), and the area under the curve (AUC). Moreover, a summary receiver operating characteristic (SROC) curve and likelihood ratio dot plot were plotted. Study-between statistical heterogeneity was evaluated via I -square index ( I 2 ). Subgroup analyses were used to explore heterogeneity. Results . Seven studies including 127 patients were involved in this meta-analysis. The overall sensitivity and specificity were 0.87 (95% CI: 0.65–0.96) with heterogeneity I 2 = 88.1% (p < 0.001 ) and 0.96 (95% CI: 0.67–1.00) with heterogeneity I 2 = 77.8% (p < 0.001 ), respectively. The pooled LR+, LR−, and DOR were 21.3 (95% CI: 2.1–213.9), 0.14 (95% CI: 0.05–0.40), and 157 (95% CI: 16–1532), respectively. The area under the SROC curve was 0.97 (95% CI: 0.95–0.98). Conclusions . Through a meta-analysis, this study suggested that 18 F-FDG PET(CT) has a good overall diagnostic accuracy in the detection of bone/BMI in pediatric neuroblastoma.